Escravidão e ensino de história no sul do Brasil: o cativo Joaquim - Schwingel, Majô (My University, 2018)
This paper analyzes the possibilities of using historical sources in the classroom. Suggestions and advices for History teachers were developed in order to be applied in educational practice. Among the questions that guide this paper we highlight: How can teachers work with historical sources in the classroom? How can a criminal proceedings be used as a pedagogical tool? What are the basic knowledge that should be developed by teachers for the use of documents in the classroom? What is continuing teacher education matter in their practice? The aim is to provide a support in order to help the teacher’s planning lessons, and also continuing education of teachers.The analysis developed in the essay accomplished in the site "Slavery and Teaching of History" where many pedagogical subsidy are available. We start from a criminal proceedings of the Rio Grande do Sul public registers (APERS) for a didactic sequence and other materials production.
Este trabalho analisa as possibilidades do uso de fontes históricas em sala de aula. Para isso, foram desenvolvidas sugestões e orientações para serem aplicadas na prática educativa por professores de História. Entre as questões que norteiam este trabalho, destacamos: Como os professores podem trabalhar com fontes históricas em sala de aula? Como um processo-crime pode ser usado como ferramenta pedagógica? Quais são os conhecimentos básicos que devem ser desenvolvidos pelos professores para o uso de documentos em sala de aula? Qual a importância da formação continuada de professores na sua prática? O objetivo é fornecer um apoio que auxilie no planejamento dos docentes e sirva também como formação continuada de professores. A análise desenvolvida na dissertação culminou no site “Escravidão e Ensino de História”, onde estão disponibilizados diversos subsídios pedagógicos. Partimos de um processo-crime do Arquivo Público do Estado do Rio Grande do Sul (APERS) para a produção de uma sequência didática e outros materiais
Keywords: História - Fontes; História - Estudo e ensino; Escravidão - Rio Grande do Sul; History - Sources; History - Study and teaching; Slavery - Rio Grande do Sul (Brazil)